PENERAPANMODEL THINK, TALK AND WRITE (TTW) DENGAN MULTIMEDIA DALAM PENINGKATAN PEMBELAJARAN IPS PADA SISWA KELAS IV SDN MANGLI TAHUN AJARAN 2015/2016 - Mulyati, Warrifadati Gita (KALAM CENDEKIA PGSD KEBUMEN, 2016)
Abstract: The Application of Think, Talk, and Write (TTW) Model Using Multimedia in Improving Social Science Learning for the Fourth Grade Students of SD Negeri Mangliin the Academic Year of 2015/2016.The objectives of this researchto improve social science learning. This research is conducted within three cycles. Each cycle consisted of two meetings including planning, action, observation, and reflection.It was proven by the increase of learning process and outcomes respectively in the first cycle 70.36% and 73.70%, in the second cycle 84.99% and 87.09%, and in the third cycle 87.09% and 91.93%.The conclusion of this research is the implementation of Think, Talk, and Write (TTW) model can improve social science learning for the fourth grade students of SD Negeri Mangli in the academic year of 2015/2016. Keywords: Think, Talk, and Write model, multimedia, social science learning.  Abstrak:PenerapanModel Think, Talk and Write (TTW) dengan Multimedia dalam Peningkatan Pembelajaran IPS pada Siswa Kelas IV SDN Mangli Tahun Ajaran 2015/2016. Tujuan penelitian ini untuk meningkatkan pembelajaran IPS. Penelitian dilakukan dalam tiga siklus dan tiap siklus terdiri dari dua pertemuan yang meliputi perencanaan, pelaksanaan, pengamatan dan refleksi. Hasil penelitian ini menunjukkan proses belajar siswa pada siklus I 70,36%, siklus II 84,99% dan siklus III 87,09%. Presentasi hasil belajar menunjukkan siklus I 73,70%, siklus II 88,33% dan siklus III 91,93%. Simpulan dari penelitian ini adalah penerapan model Think, Talk and Write dengan multimedia dapat meningkatkan pembelajaran IPS pada siswa kelas IV SDN Mangli tahun ajaran 2015/2016. Kata kunci: model think, talk and write, multimedia, pembelajaran IPS.